A guerra do Paraguai na imprensa do Rio Grande do Sul : apoio e crítica nos discursos sobre a guerra - Schäfer, Gabriel (2012)
During the 19th century, the sul-rio-grandense society lived intensely with the imperial government ambitions in the Rio de la Plata region and it was deeply influenced by the frequency with which it was involved in military conflicts. During the 1860s especially, disputes between the Brazilian Empire and the South Republics of the Rio de la Plata have emphasized irreversibly. Conflicting interests and the impossibility of understanding ended with the known and discussed War of the Triple Alliance as a final result, where, once again, the performance of the Rio Grande do Sul province, both for its geographical position and by its military personnel, had great significance. The war, of unknown proportions in the South American continent by the time, demanded a mobilization that did not go only by political and military spheres. In this effort, it is known that the press was widely used as a real combat tool in order to legitimize the speech articulated by the government, based on the defense of honor and the duty of Brazil to withdraw Solano Lopez off the power. Already established as a mean of social interaction and assuming the mission of preserving history, the press was rich in detailing the events of the war and is now an interesting alternative to look in a different perspective, the performance of Rio Grande do Sul and its society in the conflict against the Paraguayans. The way as the sul-rio-grandense elite fell within the border region and the relationship instability between the province and the Empire, evident during the nineteenth century, could at any moment turn uncertain the behavior of Rio Grande do Sul. In the records collected in 18 journals that circulated by the province between 1865 and 1870 and gathered about 67 copies total, we note a clear division in the behavior of the press ahead of the confrontation. Despite the support given to the fight for the Empire have been sharp and almost constant, manifesting itself in disqualification of the enemy and the exaltation of the Brazilian forces, there was also space for contestation and criticism in the sul-rio-grandense papers. Therefore, in moments where the province felt the most adversely affected or had not fully recognized his commitment, clear disagreements, new or old, guided the discussion. Battling the relentless effects of time, this thesis is a study about the sul-rio-grandense press and its involvement in the War of the Triple Alliance. In addition to help with the rescue of some of the valuable social and historical heritage contained in the newspapers of the time, this work seeks to understand and analyze the distinct impressions of them ahead of the long conflict, taking into account the various political and social forces that could act on them